Antioxidant and anti-inflammatory effects of cerium oxide Salvia veneris nanoparticles on acetamiprid-induced renal and hepatic toxicity - Caylak, Emrah (Polish Soc Veterinary Sciences Editorial Office, 2024)
This study investigates the antioxidant/anti-inflammatory activities of S. veneris extract (SvE) and cerium oxide nanoparticles/S. S. veneris (CeO2-NPs/SvE). The study first analyzed the total polyphenolic, flavonoid, and saponin contents of SvE. The identification of phenolic compounds was determined using High-Performance Liquid Chromatography (HPLC). Next, the study investigated the hepatoprotective and nephroprotective effects of S. veneris on acetamiprid-induced toxicity in rats. The rats were administered acetamiprid orally for two weeks, alone or in combination with SvE and CeO2-NPs/SvE. Our study found an association between acetamiprid-induced toxicity and significant changes in biochemical, histopathological, antioxidant, and anti-inflammatory parameters. The treatment with SvE and CeO2-NPs/SvE resulted in a reduction of malondialdehyde (MDA), TNF-alpha and IL-6 cytokine levels, while increasing glutathione (GSH) as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), IL-10 and TGF-beta levels. Our study suggests that cerium oxide nanoparticles synthesized from S. veneris using the green synthesis method could be a protective and therapeutic agent against various diseases.
Keywords: antioxidant; anti-inflammatory; Salvia veneris; acetamiprid; nephrotoxicity; hepatotoxicity